Nucleation of cholesterol monohydrate crystals from hepatic and gall-bladder bile of patients with cholesterol gall stones. Issue 9 (September 1983) - Gollish, S H; Burnstein, M J; Ilson, R G; Petrunka, C N; Strasberg, S M
Abstract : Nucleation time and cholesterol saturation index of hepatic and gall-bladder bile were measured in 16 patients with cholesterol gall stones to determine whether a gall bladder or liver defect was responsible for the rapid nucleation time of gall-bladder bile in such patients. Although hepatic bile was consistently more saturated than gall-bladder bile, the in vitro nucleation time of gall-bladder bile was more rapid. Dilution of gall-bladder bile to hepatic bile concentrations did not affect nucleation time. The results indicate that the gall bladder plays an important role in the production of the rapidly nucleating bile which is found in patients with cholesterol gall stones, and that this role is not simply concentration of bile by the gall bladder. Normal and abnormal gall-bladder biles were also compared in a larger group of patients. The view that there is a nucleation defect in cholesterol cholelithiasis which is independent of cholesterol saturation was confirmed. Subgroups of normal and gall-stone population were defined by the nucleation time and saturation index. Results suggested that solitary stones may be produced under different conditions than multiple stones. Some putative nucleating factors were examined but none was found to distinguish between normal and gall-stone bile.